2014
DOI: 10.1248/bpb.b14-00254
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Interaction of Nilotinib and Imatinib with P-Glycoprotein in Intracellular Accumulation and Cytotoxicity in CML Cell Line K562 Cells

Abstract: Nilotinib, a second-generation tyrosine kinase inhibitor (TKI), has been approved for first-line chronic myeloid leukemia (CML) treatment. The improved clinical response of nilotinib over that of the first generation TKI, imatinib, has been thought to be a result of its high potency of inhibition of BCR-ABL kinase. This study aimed to characterize differences between nilotinib and imatinib in the intracellular accumulation and cytotoxic effect on the CML cell line K562. Accumulation of nilotinib in K562 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…These results are consistent with results of previous studies showing that nilotinib was weaker than imatinib or dasatinib as a substrate for MDR-1. 13,14,31,32) Our results also showed that nilotinib has a stronger and longer continuous cytostatic effect than that of dasatinib. Nilotinib has a longer half-life than that of dasatinib, and MDR-1 is thought to have a lower affinity than dasatinib as a substrate.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…These results are consistent with results of previous studies showing that nilotinib was weaker than imatinib or dasatinib as a substrate for MDR-1. 13,14,31,32) Our results also showed that nilotinib has a stronger and longer continuous cytostatic effect than that of dasatinib. Nilotinib has a longer half-life than that of dasatinib, and MDR-1 is thought to have a lower affinity than dasatinib as a substrate.…”
Section: Discussionsupporting
confidence: 71%
“…Effects of ABC transporters (MDR-1 (P-gp), BCRP) on the cytostatic effects of TKIs used clinically for CML therapy were observed in previous studies, but sufficient consideration was not given to clinically confirmed plasma concentrations and half-lives of drugs in most studies. 13,14,33) Our results showed that the experimental conditions of our study closely reflect clinical conditions and that dasatinib and nilotinib had sustained cytostatic effects after drug washout with short-term exposure. We also investigated how MDR-1 expression affects the continuous cytostatic effects of TKIs and we found that dasatinib had an attenuated inhibitory effect on cell proliferation due to decreased intracellular accumulation but that nilotinib did not.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Organic cation transporter 1 and organic-anion transporting polypeptide 1A2 were shown to mediate imatinib uptake in chronic myelogenous leukemia cells (13)(14)(15). Nilotinib uptake was shown to be enhanced by organic cation transporter 1 but not by organicanion transporting polypeptide 1A2 (16). The cellular uptake of dasatinib was mainly passive and not dependent on organic cation transporters (9).…”
mentioning
confidence: 97%